2020
DOI: 10.3390/ani10020202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Vibroactivated Clinoptilolite Supplementation on the Intramammary Microbiological Findings in Dairy Cows

Abstract: The aim of this study was to determine the effects of dietary vibroactivated clinoptilolite supplementation on the intramammary microbiological findings in dairy cows, causative agents of potential intramammary infection, and their sensitivity to antibiotics. Cows (n = 78) were randomly divided into two groups: CPL-treated group that received clinoptilolite (CPL) in-feed (n = 38), i.e., 50 g natural powdered zeolite CPL, twice daily from the seventh month of pregnancy to 75 days after calving, and the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…NEB leads to irreversible pathophysiological damage such as future infertility if not minimized during the transition period. Previous studies have suggested that CPL dietary supplementation may improve energy status and reproductive efficiency during the postpartum period in cows [23][24][25]. The effect of long-term use of CPL have also been investigated, on different physiological statuses such as improved rumen digestion, increased glucose level, reduced subclinical ketosis, and reduced oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…NEB leads to irreversible pathophysiological damage such as future infertility if not minimized during the transition period. Previous studies have suggested that CPL dietary supplementation may improve energy status and reproductive efficiency during the postpartum period in cows [23][24][25]. The effect of long-term use of CPL have also been investigated, on different physiological statuses such as improved rumen digestion, increased glucose level, reduced subclinical ketosis, and reduced oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the impact of dietary vibroactivated and micronized clinoptilolite feeding in the incidence of intramammary infections was evaluated in dairy cows. It was observed that the antibacterial, antioxidative, immunostimulating and detoxifying potential of vibroactivated and micronized zeolite clinoptilolite reduced the incidence of intramammary infections (Đuričić et al 2020 ). Strategies have to be developed for using targeted nutrition to obtain positive host response in managing diseases.…”
Section: Management Of Mastitismentioning
confidence: 99%
“…Nutritional strategies have emerged, and they have been proposed as a key factor to improve the health status and welfare of animals, as well as to enhance productivity of livestock [ 2 , 3 , 4 ]. Feed additives, which are nutrients that when added to the feed can trigger the desired response of the animal’s body on production parameters, have been widely used in animal nutrition for quite a long time [ 5 , 6 , 7 , 8 ]. The main compounds used for this purpose are fermented feed, probiotics, prebiotics, synbiotics, or various types of residues from plant production.…”
Section: Introductionmentioning
confidence: 99%